Semisynthetic insulin analogues modified in positions B24, B25 and B29 - Svoboda, I; Brandenburg, D; Barth, T; Gattner, H G; Jirácek, J; Velek, J; Bláha, I; Ubik, K; Kasicka, V; Pospísek, J (Biological chemistry Hoppe-Seyler, 1994)
New semisynthetic analogues of human insulin, modified in the C-terminal region of the B-chain, were prepared to refine our understanding of the importance of particular amino acid residues in the expression of hormone biological properties. The following insulin analogues were synthesized by trypsin-catalyzed peptide-bond formation between the C-terminal arginineB22 of des-octapeptide(B23-B30)-insulin and synthetic octapeptides with the epsilon-amino group of lysineB29 protected by a phenylacetyl group: [L-Lys(Pac)B29]insulin, [D-PheB24,B25,L-Lys(Pac)B29]insulin and [D-Phe(p-Et)B24, L-Lys(Pac)B29]insulin. Enzymatic deprotection using immobilized penicillin amidohydrolase yielded: human insulin, [D-PheB24,B25]insulin and [DPhe(p-Et)B24]-insulin. Biological in vitro potencies (specific binding to cultured human lymphocytes IM-9 and lipogenic potency in isolated rat adipocytes) of the semisynthetic analogues were estimated, ranging from 0.2 to 100% relative to porcine insulin.
Keywords: lysin; Humans; Mass Spectrometry; Lymphocytes; lymfocyty; Structure-Activity Relationship; chromatografie iontoměničová; vztahy mezi strukturou a aktivitou; Lysine; Molecular Sequence Data; molekulární sekvence - údaje; krysa rodu Rattus; lidé; zvířata; receptor inzulinu; Cells, Cultured; peptidy; aminokyseliny; Amino Acids; Peptides; Amino Acid Sequence; Adipocytes; tukové buňky; Chromatography, Ion Exchange; Insulin; kultivované buňky; Receptor, Insulin; Rats; penicilinamidasa; Animals; Penicillin Amidase; hmotnostní spektrometrie; inzulin; sekvence aminokyselin